OBSERVASI GALUR HARAPAN PADI RAWA LEBAK BERDASAR POTENSI HASIL DI KABUPATEN OGAN KOMERING ILIR PROVINSI SUMATERA SELATAN - Suparwoto, Suparwoto (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2008)
The experiment was conduted at Kijang Ulu village, Kayuagung sub district during dry season 2006. The objective was to find information of several rice promissing lines. The result showed that there were 8 rice genotypes which have hight yield potential than local variety (Sei Putih). The productivity of them were 3.9 to 5,6 ton/ha. The yield potential of Sei Putih variety is lower than KAL 9414 F-M-2-KN-0 (30%), B 9852 E-KA-66 (53%), B 9833 E-KA-66 (60%), IR 70181-5-PM-1-1-2-B-1 (63%), IR 69502-6-SKN-UBN-1-B-1-3 (70%), B 10214 F-TB-7-2-3 (73%), IR 70213-9-CPA-12-UBN-2-1-3-1 (87%), B 7003 D-MR-24-3-1 (87%).